Construção das transmasculinidades: memórias e narrativas - Cardoso, Thomas Victor Barreto (Universidade Federal de São Carlos, 2022)
From the 1970s onwards, studies on masculinities gained strength, driven mainly by the feminist movement and the movement in defense of sexual diversity. But only in the last two decades, transmasculine identities began to be included in these studies on masculinities. The objective of this research is to analyze the construction of these masculinities in individuals who identify themselves as transmasculine, through their narratives and memories. Reflect on the way in which these identities are incorporated directly and indirectly by them, transforming behaviors and physiognomies to achieve a hegemonic masculine ideal, in an attempt to belong, or reject themselves, as a form of resistance. As well as the possibility of creating new ways of experiencing masculinity outside the sex-gender dichotomous view. As a methodology, thematic oral history was adopted, to focus on the memories and experiences of these individuals, and their process of construction and deconstruction together with a bibliographic review. Using authors such as Michael Foucault (2018; 2019), Berenice Bento (2011; 2017), Guacira L. Louro (2015; 2018), Paul B. Preciado (2018), Raewyn Connell (1995; 2013; 2015), Benedito Medrado (2008), Pedro P. de Oliveira (2004), João Nery (2013;2017) and Guilherme Almeida (2012) for theoretical deepening in discussions about gender, masculinities, body, identity and gender violence. In the narratives, it was noticed that even understanding masculinity as a social construction, there is still influence of it in the production of their subjectivities and corporeity. In addition to directly and indirectly reproducing gender patterns as a form of protection and/or an attempt to belong.
Construction of transmasculinities: memories and narratives
Keywords: Transmasculinidades; Corpo; Memórias; Masculinidades; Body; Masculinities; Memoirs; Transmasculinities; CIENCIAS SOCIAIS APLICADAS